Use of Rheumatology Laboratory Studies Among Primary Pediatricians. (December 2016) - Correll, Colleen K.; Spector, Logan G.; Zhang, Lei; Binstadt, Bryce A.; Vehe, Richard K.
Rheumatology laboratory tests are often inappropriately ordered in situations for which they are of low diagnostic utility. We surveyed pediatricians to investigate reasons for ordering these tests. The response rate was 15.3% (93/609). The most commonly ordered tests were antinuclear antibody (ANA), anti-double-stranded DNA (dsDNA) antibody, and rheumatoid factor (RF). Of the 89% (83/93) who ordered an ANA, 86% ordered it for correct/possibly correct reasons; of the 73% (68/93) who ordered RF, 80% did so for correct/possibly correct reasons; and among the 59% (54/92) who had ordered anti-dsDNA antibody, 34% ordered it for correct reasons. A positive relationship was seen between years since residency completion and correct use of ANA. However, positive associations were not seen between measures of pediatric rheumatology experience and correct use of other tests. Interventions are needed to improve pediatricians' utilization of rheumatology tests.